At Westonci.ca, we provide reliable answers to your questions from a community of experts. Start exploring today! Experience the ease of finding accurate answers to your questions from a knowledgeable community of professionals. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.

Solve for v.

(v-1)^2 = 2v^2 -5v -17

If can be more than one solution or no solution



Sagot :

             (v - 1)² = 2v² - 5v - 17
     (v - 2)(v - 2) = 2v² - 5v - 17
v² - 2v - 2v + 4 = 2v² - 5v - 17
       v² - 4v + 4 = 2v² - 5v - 17
    - v²                  - v²              
            -4v + 4 = v² - 5v - 17
          + 5v              + 5v       
               v + 4 = v² - 17
                  + 17     + 17
             v + 21 = v²
                     0 = v² + v + 21
      v² + v + 21 = 0
                     v = -(1) +/- √((1)² - 4(1)(21))
                                           2(1)
                     v = -1 +/- √(1 - 84)
                                      2
                     v = -1 +/- √(-83)
                                    2
                     v = -1 +/- 9.11i
                                    2
                     v = -1 + 4.555i
                     v = -1 + 4.555i        v = -1 - 4.555i

There is more than one solution.

Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.